Fractal characterization of pore–fracture in low-rank coals using a low-field NMR relaxation method. (1st October 2016) - Zhou, Sandong; Liu, Dameng; Cai, Yidong; Yao, Yanbin
Highlights: The low-field NMR fractal dimensions were measured. Effect of the D NMRA on CBM adsorption capability was performed. The permeability and D NMRM model was obtained. Characteristics of T 2 distribution and permeability were analyzed. Abstract: To describe a low-field nuclear magnetic resonance (NMR) method for quantifying pore–fracture fractal dimensions and their influence on effective porosity and permeability, we performed modeling comparisons between fractal analysis and pore–fracture physical properties in low-rank coals. The adsorption space fractal ( D NMRA ), seepage space fractal ( D NMRS ) and moveable fluid space fractal ( D NMRM ) were calculated to be 1.62–1.91, 2.77–2.98 and 1.56–2.75, respectively. The D NMRA generally increased with increasing Langmuir volume ( V L, 9.54–31.06 m 3 /t), Langmuir pressure ( P L, 0.58–8.13 MPa), the Brunauer–Emmett–Teller (BET) surface area and its fractal dimension. Higher D NMRA indicated the significant coalbed methane (CBM) adsorption capability. Both the D NMRS and D NMRM decreased with increasing areas of T 2  > 2.5 ms distribution ( S T and S CT ) and sorting coefficient. These phenomena showed that the NMR fractal method could reflect the coal pore–fracture heterogeneity and had significant influence on seepage space content. The correlations of moveable fluid porosity and permeability with D NMRM can be found by performing the models of y  =  ax  +  b ( a  < 0), so coals with high D NMRM occur to have low flow capability. Furthermore, the pore–fracture porosity and permeability have positive correlations with S T and S CT, which result from the connection between pores and fractures. These results also show that fractal analysis calculated with T 2 can be developed to appraise the physical properties of low-rank coals and supply some reference for a relatively full identification of porous media. We advise that low-field NMR can be employed as a lossless analytic method to quantify moveable fluid space fractal theory.